Construction of rGO/Bi2MoO6 2D/2D nanocomposites for enhancement visible light-driven photocatalytic reduction of Cr (VI). (14th September 2018) - Xiao, Jie; Zhang, Jinhua; Liu, Wenchen; Huang, Tianqi; Qu, Yang; Chen, Hao; Lin, Zhidong
Abstract: 2D/2D stacking heterostructures are highly desirable in constructing efficient photocatalysts. In this paper, reduced graphene oxide and Bi2 MoO6 2D/2D nanocomposites were achieved by a two-step hydrothermal method. The combined characterizations including x-ray diffraction, Raman, scanning electron microscopy and transmission electron microscopy indicated the successful formation of rGO/Bi2 MoO6 plate-on-plate heterojunction structure, where Bi2 MoO6 nanosheets with average size about 100–200 nm dispersed on the surface of large-size graphene plates. According to the test of photocatalytic activity, rGO/Bi2 MoO6 compositions exhibited an excellent photocatalytic capacity to Cr (VI) reduction. The composite containing 2.5% rGO shows the optimal photocatalytic activity, and its reduction rate to Cr (VI) is 94% in 30 min, twice higher than that of pure Bi2 MoO6 . The visible light absorption increasing and the improving of charge-carrier transference result in good photocatalytic performance of 2D/2D rGO-Bi2 MoO6 .